KSHARASUTRA (MEDICATED SETON) TREATMENT IN PILONIDAL SINUS - Sudesh, *Gupta; Bala, Madhu; Bhawana, Gupta; Manpreet, Singh (International Journal of Ayurveda and Pharma Research, 2017)
Pilonidal sinus is a disease which causes great suffering and pain to the patient. Persistence of Pilonidal sinus has given a challenge to most indigenous surgeons. This disease manifest itself as a blind track leading down to the tissues ending blind internally and discharging sero-purulent material associated with severe pain. In modern medicines, the treatment of pilonidal sinus includes excision and primary closure of excision with reconstructed flap. The risk of recurrence or of developing an infection of the wound after the operation is high. Kshara sutra is an age old treatment modality practiced since times of Sushruta. A total of 10 patients were selected with complaints of Pain, Discharge, tenderness and induration. The patients with multiple sinuses, previous treatment and co-morbid conditions were excluded. The study factor was of Kshar sutra threading of Pilonidal Sinus done under local infiltration of anaesthesia around the tract and changed every week during entire treatment period. In this study all patients were males within age of 21-30 years and median presentation duration of 10 months were recruited. The median of initial length of track was 2.4cm and median average unit cutting time revealed 6.3days / cm. There was no post-operative complication and recurrence after three months of follow up. The study revealed highly significant results in terms of Pain, Discharge, tenderness and induration. Apamarga Ksharasutra as a modality could be a minimal invasive procedure done under local anaesthesia as outpatient or day care procedure, cost effectiveness, patient can carry out his day today works, without any side effects and complications with good wound healing potential in selected group of patients. Ksharasutra being laced with antibiotics and anti-inflammatory properties also minimizes the uses of antibiotics and analgesics.